Australia and Viet Nam : development cooperation program 1999-2001, a better future through partnership. - Australian Agency for International Development (Canberra, A.C.T. : Australian Agency for International Development, 1999)
Viet Nam faces many challenges in sustaining its growth and in securing further development. In tackling these challenges, Viet Nam today is reviewing its domestic policies, and seeking to integrate more closely with the regional and international communities. Australia, as a prosperous, outward-looking nation with a strong interest in the stability and development of the Asia Pacific region, is well placed to work as a partner with Viet Nam in its pursuit of poverty reduction and sustainable development. This paper provides an overview of Australia's development cooperation program, which assists Viet Nam to reduce poverty and achieve sustainable economic and social development for its people.
Development context - Australia's national interest - Current program - Future program strategy - Key relationships - Performance monitoring & evaluation - annex 1. Poverty analysis and social conditions - annex 2. The economic situation - annex 3. The state of the environment - annex 4. Gender issues in Viet Nam.
"October 1999"
Includes bibliographical references [p. 37-40]
Also available in PDF format via the Internet at: http://www.ausaid.gov.au/publications/pdf/vietnam_devcoprog1999-2001.pdf
Keywords: Technical assistance, Australian -- Vietnam; Economic assistance, Australian -- Vietnam; Australia -- Foreign relations -- Vietnam; Vietnam -- Foreign relations -- Australia; Vietnam -- Economic conditions